Cube Therapy Application in Gout Patients - Dimas Arindha Sutrisno; Dwi Retnaningsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
When uric acid crystals accumulate in the body's joints as a result of excessive consumption, gout develops. Three types of treatments are used to manage gout patients: pharmaceutical, non-pharmacological, and complementary treatments. Use pharmaceuticals such NSAIDs, cholcicine, and corticosteroids for pharmacology. By consuming low-purine diets and doing mild exercise, for non-pharmacological. Cupping is another supplementary therapy technique. This study sought to ascertain whether cupping may lower uric acid levels in gout patients in Tunjungharjo, Grobogan. A case study research methodology with a pre-study and pretest-posttest design was employed in this study. The sampling technique that was used was purposive sampling. Four people who met the inclusion criteria were the case study's four subjects high uric acid clients, defined as men >7 mg/dl and women >6 mg/dl. Data collected from uric acid levels before and after cupping intervention. Data analysis is done by presenting facts, then by comparing existing theories and putting them into discussion opinions. According to the findings, 75% of the responders had uric acid levels above 6.0 mg/dl prior to cupping. All (100%) of the responders saw a drop in uric acid levels after cupping, it was discovered. According to the study's findings, cupping helps gout patients with lower uric acid levels.